FORMATION OF THE INTERACTIVE COMPETENCE OF FUTURE TEACHERS IN TERMS OF MEANINGFUL CRITERION - Пикус, Дмитрий; Герич, Владимир; Теслюк, Валентина (SWorldJournal, 2021)
The article reveals a study of the content criterion of the formation of interactive competence in future teachers of higher education. It is established that the criteria for the formation of interactive competence of the future teacher are: motivational